2016
DOI: 10.1093/mnras/stw3148
|View full text |Cite
|
Sign up to set email alerts
|

Structure and evolution of the diamagnetic cavity at comet 67P/Churyumov–Gerasimenko

Abstract: The long duration of the Rosetta mission allows us to study the evolution of the diamagnetic cavity at comet 67P/Churyumov-Gerasimenko in detail. From April 2015 to February 2016 665 intervals could be identified where Rosetta was located in a zeromagnetic-field region. We study the temporal and spatial distribution of this cavity and its boundary and conclude that the cavity properties depend on the long-term trend of the outgassing rate, but do not respond to transient events at the spacecraft location, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 35 publications
4
91
0
Order By: Relevance
“…Figure 5a shows a bar chart of the number of cavity crossings each day during this period (the conspicuous coloring will be explained in connection with Figure 6 below). The distribution is very uneven, with most cavity events occurring in clusters in the end of July, early August, and the end of November 2015, as previously noted by Goetz, Koenders, Hansen, et al (2016) and Henri et al (2017). This is even more clear in Figure 5b, which shows a bar chart of the total time spent inside the cavity during each day.…”
Section: Statistical Survey Of All Cavity Crossingsmentioning
confidence: 60%
See 2 more Smart Citations
“…Figure 5a shows a bar chart of the number of cavity crossings each day during this period (the conspicuous coloring will be explained in connection with Figure 6 below). The distribution is very uneven, with most cavity events occurring in clusters in the end of July, early August, and the end of November 2015, as previously noted by Goetz, Koenders, Hansen, et al (2016) and Henri et al (2017). This is even more clear in Figure 5b, which shows a bar chart of the total time spent inside the cavity during each day.…”
Section: Statistical Survey Of All Cavity Crossingsmentioning
confidence: 60%
“…It should be short enough for secularly varying parameters such as comet outgassing, latitude, and radial distance of the spacecraft to be constant but still long enough to contain sufficient measurements for good statistics. The diamagnetic cavity events came in the form of single events and clusters; the most prominent clusters occurred on 30 July 2015 and 19–21 November 2015 (Goetz, Koenders, Hansen, et al, ). We found that the 50‐hr interval between 08:00 on 19 November 2015 and 10:00 on 21 November 2015 fulfilled the above criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…is shown in Figure . These waves were detected close to the comet diamagnetic cavity (Goetz, Koenders, Hansen, et al, ; Goetz, Koenders, Richter, et al, ). The individual wave cycles are asymmetric and have steepened edges on the left‐hand side.…”
Section: Resultsmentioning
confidence: 98%
“…This neutral atmosphere gets ionized by photoionization and electron impact ionization, and the newly born ions get picked up and accelerated by the convective electric field of the solar wind (e.g., Cravens & Gombosi, 2004;Galand et al, 2016;Szegö et al, 2000). From April 2015 to February 2016 Rosetta intermittently encountered a magnetic field free region, known as the diamagnetic cavity (Goetz, Koenders, Hansen, et al, 2016;Goetz, Koenders, Richter, et al, 2016). Both the accelerated population and a relatively cold population with low bulk velocity are observed with RPC-ICA (Nilsson, Stenberg Wieser, Behar, Simon Wedlund, et al, 2015;Nilsson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%